2017
DOI: 10.1007/s13410-017-0585-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic index: challenges in translating concept to practice

Abstract: Dietary prescribing in diabetes mellitus based on glycaemic index (GI) of foods has always been an attractive concept. Food choices with lower GI are associated with lower glucose responses after consumption and hence would be the preferred choices in patients with diabetes. While this idea has been very promising, the real challenge over the years has been its implementation in day to day practice. Several issues like validity and reproducibility of GI measurements, factors affecting glycaemic responses, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Education about the glycemic index of food to diabetic patients is needed as a diabetes prevention and control measure. Good knowledge of the glycemic index needs to be possessed by diabetic patients as a basis for good practice in controlling dietary patterns [20]. The previous studies have shown that most diabetic patients have insufficient knowledge, so education in diabetes management is needed [21].…”
Section: Discussionmentioning
confidence: 99%
“…Education about the glycemic index of food to diabetic patients is needed as a diabetes prevention and control measure. Good knowledge of the glycemic index needs to be possessed by diabetic patients as a basis for good practice in controlling dietary patterns [20]. The previous studies have shown that most diabetic patients have insufficient knowledge, so education in diabetes management is needed [21].…”
Section: Discussionmentioning
confidence: 99%
“…The study result of (Zafar et al, 2019) has proved that the low-GI diets reduce glycated hemoglobin (HbA1c) levels, fasting blood glucose levels, BMI, total cholesterol, and LDL, but had no effect on fasting insulin, HOMA-IR, HDL, triglycerides, or insulin requirements. Even with these limitations, GI continues to capture the attention of physicians and nutritionists alike as it does offer a rational way of ranking carbohydrate-containing foods that has the potential to favorably affect the prevention and management of diabetes (Madhu, 2017). Idli, a South Indian staple diet which had been into controversies in recent times, has been acknowledged as a wholesome, nutritious food by many health professionals.…”
Section: Introductionmentioning
confidence: 99%